Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Konsumen Di Pasar Buana Impian Di Kota Batam - Nanda Harry Mardika (LPPM Universitas Putera Batam, 2023)
The purpose of this study is to determine the effect of the Location and the Price on consumer Purchase Decisions on Buana Impian Shock Market in Batam City either partially or simultaneously. The independent variable of this research is Location and Price and the dependent variable is Purchase Decision. The population of this research was people who have bought in this market. Samples of this study were taken by using accidental sampling. The technique of collecting data from this study is by using questionnaires. Methods of data analysis in this study using multiple linear regression analysis with the help of statistical software SPSS. The results of this study are the Location has negative and insignificant effect on Purchase Decisions with coefficient -0.251. Prices has positive and significant influence on Purchase Decisions with a coefficient of 0.564. F test results indicate the Location and Price simultaneously have positive and significant influence on Consumers purchase decisions on Buana Impian Shock Market in Batam City. The value of F count 5.408>3.18 and significance value 0.007<0.05 then Ho is rejected and Ha accepted. Value t count -1.380<2.00758 shows the Location has insignificant and negative influence on Purchase Decisions, with significant value 0.174>0.05 then Ho is accepted and Ha rejected. Price has positive and significant influence on Purchase Decisions by value t count 2.400> 2.00758 and the significance value 0.020<0.05 then Ho is rejected and Ha accepted.